2020
DOI: 10.1080/22221751.2020.1772678
|View full text |Cite
|
Sign up to set email alerts
|

ddPCR: a more accurate tool for SARS-CoV-2 detection in low viral load specimens

Abstract: Quantitative real time PCR (RT-PCR) is widely used as the gold standard for clinical detection of SARS-CoV-2. However, due to the low viral load specimens and the limitations of RT-PCR, significant numbers of false negative reports are inevitable, which results in failure to timely diagnose, cut off transmission, and assess discharge criteria. To improve this situation, an optimized droplet digital PCR (ddPCR) was used for detection of SARS-CoV-2, which showed that the limit of detection of ddPCR is significan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
340
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(355 citation statements)
references
References 19 publications
10
340
1
4
Order By: Relevance
“…As of today, few studies reported the use of ddPCR for a more sensitive SARS-CoV-2 detection compared to RT-PCR 12 , 14 16 . To our knowledge, this is the first report of direct quantitation of SARS-CoV-2 RNA performed on a consistent number of clinical samples and comparing two different nasopharyngeal swabs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of today, few studies reported the use of ddPCR for a more sensitive SARS-CoV-2 detection compared to RT-PCR 12 , 14 16 . To our knowledge, this is the first report of direct quantitation of SARS-CoV-2 RNA performed on a consistent number of clinical samples and comparing two different nasopharyngeal swabs.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the droplet digital PCR (ddPCR) might be more appropriate for quantitation of viral loads, as previously reported 7 . The ddPCR allows precise quantitation of nucleic acid copies without the need of a calibration curve and with higher resistance to the amplification inhibitors, compared to the quantitative real-time PCR 8 ; some recent studies reported the usage of ddPCR for the quantitation of SARS-CoV-2 9 16 . However, all the described ddPCR procedures included a RNA extraction/purification step, leading to potential amplification errors, due to variable and suboptimal nucleic acid yields 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…An overall accuracy of 94.3% was obtained, ∼500 times more sensitive than RT-PCR. 68 Lu et al compared the RT-dPCR and RT-PCR with 108 specimens (pharyngeal swab, stool, and blood) longitudinally collected from 36 COVID-19 patients. The RT-dPCR showed the detection limit 10× lower than that of RT-PCR.…”
Section: Dpcrmentioning
confidence: 99%
“…While reverse-transcriptase RT-PCR is still the gold standard, the ndings in the present study indicate that the assay sensitivity of the RT-PCR assay is reduced due to background NA from the patient sample. By contrast, the sensitivity of the RT-ddPCR multiplex assay was not affected by background NA, and is more sensitive than the gold standard reverse-transcriptase RT-PCR [4][5][6][7] in the clinical setting.…”
Section: Discussionmentioning
confidence: 89%
“…Another approach is to detect the nucleocapsid (N) gene, and to use an open reading frame 1a/b (ORF1b) gene or E gene assay as a con rmatory test [3]. In addition, to improve assay sensitivity, other studies have been focusing on the detection of N, E or ORF1b using droplet digital polymerase chain reaction (ddPCR) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%